Gastric Schwannoma Diagnosed by Endoscopic Ultrasonography-Guided Trucut Biopsy - Hong, Sung Wook (The Korean Society of Gastrointestinal Endoscopy, 2013)
Schwannomas of the gastrointestinal (GI) tract are rare subepithelial tumors comprising approximately 3.3% to 12.8% of all mesenchymal tumors of the GI tract. On endoscopic ultrasound (EUS) they are seen as hypoechoic tumors arising most commonly from the 4th proper muscle layer. Although EUS helps to distinguish tumor characteristics, tissue sampling is required for differentiation with other more common tumors such as GI stromal tumors. Both EUS-guided fine needle aspiration and EUS-guided trucut biopsy (EUS-TCB) can be used for tissue sampling. However, only EUS-TCB allows core biopsy and a high yield of immunohistochemical staining. We report a case of a gastric schwannoma diagnosed by EUS-TCB.